PELATIHAN PEMBELAJARAN AKTIF BERBANTUAN “BLOK ALJABAR” BAGI GURU SMP N 1 PONDOK KELAPA - Nurul Astuty Yensy (DHARMA RAFLESIA, 2018)
The majority of teacher in SMP N 1 Pondok Kelapa Central Bengkulu still have difficulty how to organize the effective learning. Very rarely do they plan mathematic learning with a real-life approach that enable the student, because they assume that such learning was useless, confusing and time-consuming. Based on the preliminary survey found that in SMP N 1 Pondok Kelapa, the teacher in there still used a conventional method in learning. The teacher rarely used the prop as learning media, as in the matter of quadratic equation. Whereas making innovative and creative mathematical tool was so easy to be created, so that in this activity  have done "The training of active learning by using block of algebra for teacher of high school in SMP N 1 Pondok Kelapa. Block of Algebra was a learning tool of matter of quadratic equation. The method used in this activity include: workshop, demonstration, discussion, and Monitoring and Evaluation. Before the activity was done, All of teacher did not have knowledge how to make prop "algebra block". After the workshop was conducted and after completing the practice of making the prop in school, about 84% (5 groups from 6 groups of teacher) produced better and applicable prop. While the other group had not finished completing the "algebra block" prop because of technical error, but in general (about 95%) the teacher' response to this activity was excellent and their knowledge of the making of algebra block prop increased. Keywords: Block of Algebra, active learning